The impact of assisted reproductive technology in twin pregnancies complicated by intrahepatic cholestasis: a five-year retrospective study - Qianwen Zhang; Yu Xu; Yunhui Gong; Xinghui Liu (BMC Pregnancy and Childbirth, 2022)
Abstract Background Intrahepatic cholestasis of pregnancy is one of the common complications during pregnancy, and ursodeoxycholic acid has been recommended as the first-line drug. However, if the assisted reproductive technology may increase adverse perinatal outcomes of twin pregnancies complicated by intrahepatic cholestasis is disputed, we aimed to investigate perinatal outcomes between twin pregnancies by assisted reproductive technology versus spontaneous conception, based on these women accepted ursodeoxycholic acid treatment. Methods From January 2014 to January 2019, we retrospectively analysed the clinical data of twin pregnant women with intrahepatic cholestasis, excluding those who did not receive ursodeoxycholic acid treatment. In total, 864 women were included, among whom 500 conceived by assisted reproductive technology and 364 conceived by spontaneous conception. The primary assessment for perinatal outcomes included premature birth, meconium-stained amniotic fluid, low Apgar score, neonatal intensive care unit and still birth, and secondary indicators were serum bile acid and liver enzymes level during medication, so we also finished subgroup analysis based on different elevated bile acid level and drug usage. The statistical analysis was performed by SPSS 22.0. Results The study demonstrated that compared to spontaneous conception, assisted reproductive technology conceived twin pregnancies diagnosed as intrahepatic cholestasis earlier (p = 0.003), and lower birth weight (p = 0.001), less incidence of preterm delivery (p = 0.000) and neonatal intensive care unit admission (p = 0.001), but the rate of meconium-stained amniotic fluid, low Apgar score and still birth have no statistic differences. Moreover, the subgroup analysis showed no significant difference in elevated bile acid levels and medication between assisted reproductive technology and spontaneous conception groups. Conclusions The assisted reproductive technology may increase the risk of early-onset intrahepatic cholestasis in twin pregnancies, but it does not seem to increase adverse effects on bile acid levels and perinatal outcomes. Regardless of ursodeoxycholic acid used alone or combination, the effect of bile acid reduction and improving perinatal outcomes in twin pregnancies is limited. Our conclusions still need more prospective randomized controlled studies to confirm.